2013 10th IEEE International Conference on Control and Automation (ICCA) 2013
DOI: 10.1109/icca.2013.6565050
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of packed tower liquid desiccant dehumidifier based on LSSVM

Abstract: In this paper, an empirical model based on least square support vector machine (LSSVM) method to predict the output air conditions in a packed tower liquid desiccant dehumidifier is developed. By analysis of the coupled heat and mass transfer between the process air and desiccant solution, six variables are used as the inputs of the LSSVM model, namely: desiccant solution and air flow rates, desiccant solution and air inlet temperature, desiccant concentration, and air relative humidity. Meanwhile, outlet air … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The research on air dehumidification by LDDSs may trace back to 1955 when Lof first designed an open-cycle air-conditioning system using triethylene glycol as a liquid desiccant. Since then, numerous papers have reported contributions to the system design of the LDDS, experimental investigation, performance analysis, and coupled heat mass transfer model development. , Li et al presented both single-stage and double-stage photovoltaic-electrodialysisa (PV-ED) regeneration systems to further explore the energy saving potential of LDDSs, and the comparison results showed that the double-stage system was more energy efficient with more than 50% energy saving . The performance of an electrodialysis (ED) regenerator was experimentally studied to obtain the effects of different flow rates of desiccant solution on the current utilization and mass transfer rate on unit area of the anion-exchange membrane regenerator .…”
Section: Introductionmentioning
confidence: 99%
“…The research on air dehumidification by LDDSs may trace back to 1955 when Lof first designed an open-cycle air-conditioning system using triethylene glycol as a liquid desiccant. Since then, numerous papers have reported contributions to the system design of the LDDS, experimental investigation, performance analysis, and coupled heat mass transfer model development. , Li et al presented both single-stage and double-stage photovoltaic-electrodialysisa (PV-ED) regeneration systems to further explore the energy saving potential of LDDSs, and the comparison results showed that the double-stage system was more energy efficient with more than 50% energy saving . The performance of an electrodialysis (ED) regenerator was experimentally studied to obtain the effects of different flow rates of desiccant solution on the current utilization and mass transfer rate on unit area of the anion-exchange membrane regenerator .…”
Section: Introductionmentioning
confidence: 99%